MASHED OF PEGAGAN LEAVES ACCELERATES THE HEALING OF BURNS ON WHITE RATS - Darmalaksana, I Gusti Ngurah; Sudimantini, Luh Made; Jayawarditha, Anak Agung Gde; Dada, I Ketut Anom (Buletin Veteriner Udayana, 2018)
Burns are an occurrence of skin tissue damage due to contact with the heat source such as fire, chemical, electrical and radiation. Wound handling was done   so that the wounds heals faster. This study aims to determine the speed of the second-degree burns healing on white rats ( Rattus norvegicus ) were given mashed of pegagan leaves ( Cantella asiatica (L) Urban ) seen from the macroscopic and microscopic descriptions. Thirty-two female white rats weighing 150-200 grams were divided into two treatments, each treatment consisting of 16 rats, area burns treatment performed on the dorsal of rats with diameter of 1 centimeters. Giving mashed of pegagan leaves as much as three sheets with the size of 2x1 centimeters. Macroscopic observation were performed daily for 14 days. On the seventh day and day 14, all rats had euthanasia , then skin burns were collected for microscopic examination.The result of macroscopic examination were analyzed by Chi-Square and Analysis of variant, whereas histopathologic examination were analyzed using the Mann-Whitney. The result of macroscopic examination of the wound diameters, inflammation marks, swelling and scarring were significantly different. Thus, by giving mashed of pegagan leaves had significant effect on the control rats. On microscopic examination were analyzed by the Mann-Whitney  were significantly different in the epithelial cells at the seventh day Giving mashed of pegagan leaves  were accelerate the healing of second degree burns on white rats.